A terminology affair: trichotillomania or trichotillotic. - Shelleh, H.H.; Asad, M.H.; Mansoor, M. (European Journal of Pediatric Dermatology, 2000)
Sometimes, a wrong term lives illegally in medical literature. It acquires its substantial life support from its current use in medical practice. Time then comes to build up a hard shell around it so that it survives. This unfortunately disappoints many academic workers in approaching and correcting the wrong term. As the latter becomes time honored, the terminology becomes a holy field surrounded by the holy rights of the first authors! Is the birth certificate of a term stronger than even a justified research, just for the priority of time? Why does a wrong term live despite swimming against the scientific current? Trichotillomania (TTM) is a second example (12). (...).